2011 11th IEEE International Conference on Nanotechnology 2011
DOI: 10.1109/nano.2011.6144623
|View full text |Cite
|
Sign up to set email alerts
|

Evolving nanoscale associative memories with memristors

Abstract: An associative memory is an essential building block for high-level networks for cognitive or brain-like computing. In this paper we consider the problem of designing associative memories using nanoscale memristors. Until now, memristors have been exploited solely as a synapse in neural networks. Our approach is novel because it exploits the analog, timedependent properties of memristors, resulting in more efficient and simpler designs. We have designed two complementary evolutionary frameworks for the automat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…If there is no current flow, the internal state will be retained. From this it follows that a memristor acts like a nonvolatile memory, whereas the range of values is continuous [14], [15]. That is an interesting fact comparable to transistor memory technology.…”
Section: Propertiesmentioning
confidence: 86%
“…If there is no current flow, the internal state will be retained. From this it follows that a memristor acts like a nonvolatile memory, whereas the range of values is continuous [14], [15]. That is an interesting fact comparable to transistor memory technology.…”
Section: Propertiesmentioning
confidence: 86%
“…If no current is applied, the internal state will be retained. It follows that a memristor acts like a nonvolatile memory, whereas the range of values is continuous [14,15]. That is an interesting fact comparable to transistor memory technology.…”
Section: Propertiesmentioning
confidence: 98%
“…This challenge has previously been addressed in many different ways, such as for example by modeling artificial neural networks with traditional components (e.g., resistors, capacitors, operational amplifiers, including voltage and current sources) [28]. We have recently evolved a 3memristor circuit [19] that can solve the simple task as outlined below.…”
Section: B Associative Memorymentioning
confidence: 99%
“…We have previously shown that simple memristor circuits can solve associative tasks [19]. However, the circuits were automatically discovered by using Genetic Programming (GP) and did not use a reservoir.…”
Section: Introductionmentioning
confidence: 99%